The Transformation of Retailing System - Vengrauskas, Vytautas; Žitkienė, Rima (Ekonomika, 2000)
The article aims at a system approach of complex transformation process of retailing with compliance of environment. structure and location changes in spatial demand variations, which arc forming not only in territorial area, but also in geographical spatial area where different elements of retailing system are functioning. The problem is that there is not foundation of conception and instruments, norms or co-ordination in retailing system development, which is a part of development process of complex post-industrial economics system. The goal of article is to analyse a function of retail in system approach reviewing environment changes and to show how inputs of the system are transformed in equifinality results. The elements of retailing system are functioning in spatial area, where they constrain in complicated solutions. The macro and micro factors influence the transformation process of retailing system, in which not only new elements. hut also reconstructed and united ones take part. The effective results of retailing system can he reached only when demand and supply arc balanced due to rational shape of retail network. Structure. property and location of retail elements arc importance factors. That’s why it is necessary to choose the right instruments, ensuring effectual of retailing system.